Cache-Aware Multi-Core Operating System Scheduler Design - Lam, Jun Wei (2009)
This dissertation proposes a solution by augmenting an existing scheduling domain hierarchy to be aware of the relationship between the processing cores and their respective LLCs in order to achieve improved performance.